2005
DOI: 10.1007/s11136-004-0798-7
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness, longitudinal- and cross-sectional construct validity of the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) in Dutch children with asthma

Abstract: The assessed properties of the PAQLQ linguistic validation into Dutch were similar to those originally established for the PAQLQ in Canada. This study showed that the Dutch PAQLQ has adequate psychometric properties, excellent responsiveness, and that the longitudinal and cross-sectional construct validity is supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 44 publications
3
59
0
Order By: Relevance
“…(22) In a validation study, the number of validity and reliability components included should be sufficient to provide an overview of its psychometric performance. (7) Correlations between the PAQLQ scores and FEV 1 were similar to what has previously been reported, (24)(25)(26) and the lack of strong correlations is no surprise. With a better understanding of the different spectra encompassed by type and health measures, correlations on the order Field-test validation of the Brazilian version of the Paediatric Asthma Quality of Life Questionnaire…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…(22) In a validation study, the number of validity and reliability components included should be sufficient to provide an overview of its psychometric performance. (7) Correlations between the PAQLQ scores and FEV 1 were similar to what has previously been reported, (24)(25)(26) and the lack of strong correlations is no surprise. With a better understanding of the different spectra encompassed by type and health measures, correlations on the order Field-test validation of the Brazilian version of the Paediatric Asthma Quality of Life Questionnaire…”
Section: Resultssupporting
confidence: 84%
“…A PubMed database search (March of 2009) for PAQLQ validation studies rendered 13 articles, 8 of which were cultural validation studies. (19,(21)(22)(23)(24)(25)(26)(27) Of those, there were two different reports of the validation of the Spanish-language version and one regarding the independent Brazilian version previously mentioned. However, among those studies, diverse methodologies were used to assess the properties.…”
Section: Resultsmentioning
confidence: 99%
“…Results are expressed as the mean score per domain as well as for overall quality of life. Raat et al 12 showed good validation of the PAQLQ in a Dutch population.…”
Section: Quality Of Lifementioning
confidence: 99%
“…However, the number of studies conducted on child QOL and asthma remains limited. The majority of studies have focused on development and validation of disease-specific QOL instruments such as the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) (Raat et al, 2005;Tauler et al, 2001), or the impact of various treatments such as inhaled corticosteroids on QOL (Lemanske et al, 2002;Murphy, Fitzpatrick, Cruz-Rivera, Miller, & Parasuraman, 2003). Few studies have focused specifically on the impact of childhood asthma on QOL.…”
Section: Quality Of Life In Children With Asthmamentioning
confidence: 99%